2005
DOI: 10.1038/sj.npp.1300664
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Regulation of Serotonergic Transmission and Behavior in 5-HT Receptor Knockout Mice

Abstract: Few studies have examined the relationship between genetics, stress, and sex-linked differences in neurotransmitter systems. Examining serotonin (5-HT) receptor knockout mice on stress-induced behavioral depression, female 5-HT 1B receptor knockout mice demonstrated significantly reduced immobility than either male 5-HT 1B receptor knockout mice or male and female wild-type mice on the tail suspension test (TST) and forced swimming test. The behavioral phenotype was identified as likely due to a disinhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(62 citation statements)
references
References 55 publications
8
52
0
Order By: Relevance
“…Insofar as the reduced immobility of female Ucn-2-deficient mice resulted primarily from an increase in swimming behavior, their antidepressant-like phenotype may be linked to altered serotonergic neurotransmission. Interestingly, female, but not male, 5-HT 1B -deficient mice also selectively show reduced immobility in the forced-swim and tail-suspension tests (Jones and Lucki, 2005), putatively through a mechanism involving disinhibition of 5-HT signaling. Furthermore, several other studies have demonstrated a differential sensitivity of females to genetic deletion or polymorphisms of modulators of serotonin function (Bouali et al, 2003;Cornelissen et al, 2005;Jones and Lucki, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Insofar as the reduced immobility of female Ucn-2-deficient mice resulted primarily from an increase in swimming behavior, their antidepressant-like phenotype may be linked to altered serotonergic neurotransmission. Interestingly, female, but not male, 5-HT 1B -deficient mice also selectively show reduced immobility in the forced-swim and tail-suspension tests (Jones and Lucki, 2005), putatively through a mechanism involving disinhibition of 5-HT signaling. Furthermore, several other studies have demonstrated a differential sensitivity of females to genetic deletion or polymorphisms of modulators of serotonin function (Bouali et al, 2003;Cornelissen et al, 2005;Jones and Lucki, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, female mice lacking 5-HT1B receptors exhibit reduced depressive behaviour, whereas male mice are similar to wild-type controls. Again, antidepressant treatment decreases immobility in both male and female 5-HT1B knockout mice (Jones and Lucki, 2005). Finally, female but not male 5-HT3 knockouts show depressive behaviour with enhanced immobility and decreased swimming levels during a second FST session (Bhatnagar et al, 2004).…”
Section: Sex Differences In Animal Models Of Depressionmentioning
confidence: 99%
“…3b, unpaired Student's t test, P ϭ 0.037, Cohen's d ϭ 0.88). Immobility in the tail suspension test (TST) is believed to reflect diminished capacity for stress-alleviating behaviors, and reduced SERT function achieved with acute SSRI treatment decreases immobility (22). Despite differences in basal TST immobility, sensitivity to citalopram (20 mg/kg) appeared identical between genotypes (shown as % reduction in immobility over saline, Fig.…”
Section: Impact Of Slc6a4 Variation In Recombinant Inbredmentioning
confidence: 99%